Sustainable Practices in Electronics Engineering: Inclusion of Virtual Reality in Product Testing - Dandeu, Juan Ignacio; Rodriguez, Facundo (My University, 2022)
Abstract— Virtual reality (VR) technologies provide novel and enhanced modes for human-computer interaction that can be used as a potential tool to provide product user experience and usability evaluation which are more efficient, even in the early stages of the product design. This paper presents a conceptual approach to virtual reality technologies application in the evaluation of usability in consumer product design. Resumen— Las tecnologías de realidad virtual (VR) brindan modos novedosos y mejorados para la interacción humano-computadora que se pueden utilizar como una herramienta potencial para proporcionar una experiencia de usuario del producto y una evaluación de la usabilidad que son más eficientes, incluso en las primeras etapas del diseño del producto. Este trabajo presenta una aproximación conceptual a la aplicación de tecnologías de realidad virtual en la evaluación de la usabilidad en el diseño de productos de consumo.
Keywords: Inglés II; virtual reality; product testing; realidad virtual; testeo de productos